21 The role of osteopontin in left ventricular hypertrophy. (1st April 1997) - Martin, Tamara P; Andrade, Maria Cobo; Loughrey, Christopher; Graham, Delyth; McBride, Martin W
Abstract : The stroke-prone spontaneously hypertensive rat (SHRSP) develops increased left ventricular mass index (LVMI) prior to the onset of hypertension, making it a fundamental model to better understand human cardiovascular disease. We identified a quantitative trait locus (QTL) for LVMI on chromosome 14 and, by using chromosome 14 congenic strains and gene profiling, have identified osteopontin ( Spp1 ) as a positional candidate gene. Here, we show 1) that Spp1 may promote cardiac remodelling via extracellular vesicle (EV) signalling and 2) provide phenotypic and molecular characterisation of a CRISPR/Cas9 Spp1-knockout rat on the SHRSP genetic background (SHRSP- Spp1 KO). 1) Briefly, H9c2 cells were seeded 24 hours prior to transfection with Spp1 cloned into pcDNA1 (5 ug) for 48 hours. EVs were isolated from conditioned media (CM) via ultracentrifugation, verified by NanoSight, re-suspended in PBS and placed onto fresh H9c2 cells for 48 hours. Crystal violet stained H9c2 cells were analysed using ImageJ. Cells transfected with Spp1 cDNA derived from the SHRSP rat displayed a significant increase in cell size compared with cells transfected with empty pcDNA vector (pcDNA 107.9±1.4 vs SHRSP 141.8±2.3, p<0.001). Similarly, conditioned media (CM) taken from SHRSP transfected cells produced a significant increase in fresh H9c2 size compared with empty pcDNA vector (pcDNA 67.9±1.1 vs SHRSP 133.0±2.9, p<0.001). EVs isolated from media conditioned from cells transfected with SHRSP significantly increased fresh H9c2 cell size compared to empty pcDNA vector (pcDNA 96.6±1.5 vs SHRSP 152.9±2.6, p<0.001). Collectively these data suggest that over-expression of Spp1 promotes an increase in cell size via EV signalling. Further studies are required to characterise EV content and the downstream mechanisms leading to hypertrophy. 2) Hemizygous rats were bred and confirmation of Spp1 gene knockout was confirmed in resultant pups by a restriction fragment length polymorphism, Sanger sequencing and ELISA. Echocardiography and radiotelemetry were used to assess cardiac function and blood pressure, respectively. Male rats were assessed over 5–16 weeks of age. Cardiac fibrosis was assessed by picro-sirus red staining of total collagen and Col1a1 mRNA expression was assessed by qRT-PCR. LVMI, calculated from either echocardiography or post-mortem, showed no significant difference in SHRSP- Spp1 KO compared to its SHRSP littermate controls (p>0.05). Similarly, no difference was observed in LV relative wall thickness in SHRSP- Spp1 KO compared to SHRSP (p>0.05). Cardiac fibrosis assessed by both histology and qRT-PCR showed no significant difference in SHRSP- Spp1 KO compared to SHRSP (p>0.05). Overall, these data suggest that the cardiac phenotype of the SHRSP- Spp1 KO rat is no different from SHRSP at baseline. Further studies are required to determine whether a cardiac stress will unmask a difference in phenotype in the SHRSP- Spp1 KO compared to littermate controls.